A novel GSK3 inhibitor that promotes self-renewal in mouse embryonic stem cells. Issue 10 (2nd October 2020) - Kobayashi, Hiroki; Nishimura, Haruna; Kudo, Norio; Osada, Hiroyuki; Yoshida, Minoru
ABSTRACT: Small molecules that regulate cell stemness have the potential to make a major contribution to regenerative medicine. In the course of screening for small molecules that affect stemness in mouse embryonic stem cells (mESCs), we discovered that NPD13432, an aurone derivative, promoted self-renewal of mESCs. Normally, mESCs start to differentiate upon withdrawal of 2i/LIF. However, cells treated with the compound continued to express endogenous Nanog, a pluripotency marker protein essential for sustaining the undifferentiated state, even in the absence of 2i/LIF. Biochemical characterization revealed that NPD13432 inhibited GSK3α and GSK3β with IC50 values of 92 nM and 310 nM, respectively, suggesting that the compound promotes self-renewal in mESCs by inhibiting GSK3. The chemical structure of the compound is unique among known molecules with this activity, providing an opportunity to develop new inhibitors of GSK3, as well as chemical tools for investigating cell stemness. GRAPHICAL ABSTRACT: uf0001 NPD13432, an aurone derivative, promotes self-renewal of mouse embryonic stem cells by inhibiting GSK3.